(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2020)
This academic paper is aimed at studying the theories that contemplate the criminal the legal-penal good in the criminal type of money laundering, provided for in Law No. 9.613/1998, with the promoted by Law No. 12,683/2012, with the formulation of objections and the contributions from each of the theoretical strands, with the aim of establishing a teleological a teleological framework for this institute. In order to ensure consistency in the final conclusion, the study the constitutional models of the State and the fundamental function of criminal law. of criminal law, also bringing conceptual and developmental considerations about criminal legal-penal good. Finally, a favorable scenario has been formed for examining the the nuances of each of the theoretical proposals that build up the contextualization of the legal-penal good in the crime of money laundering, with the aim of determining the one that best adapted, from a teleological point of view, to this criminal norm, given the relevance of its definition for so many other issues inherent in the analysis of typicality.